The Effect of an educational Intervention on Anxiety of Pregnant Women: A Quasi-Experimental Study - Pouryousef, Sajad; Jahromi, Marzieh Kargar; Yeganeh, Sedigheh; Rouhandeh, Rouhollah; Paki, Somayeh; Jokar, Mozhgan (Investigación y Educación en Enfermería, 2023)
Objective. The aim of study is the effect of educational intervention on anxiety of pregnant women. Methods. This quasi-experimental study is done on the pregnant women referring to family physician’s offices in Gerash City, Iran. 62 women were selected and divided into 2 groups (control and intervention). In intervention group the anxiety reduction training classes were held as a group discussion in 4 weekly 90-minute sessions. Control group received routine care. The anxiety assessment completed by two groups before and after the educational intervention. The measurement instruments included a demographic information questionnaire and the short form of the Pregnancy Related Anxiety Questionnaire (PRAQ-17). Results. Comparison of the mean scores of different dimensions of pregnancy anxiety in the pre-intervention and post-intervention stages in the intervention group using paired t-test indicated a statistically significant difference in the dimensions Fear of childbirth, Fear of giving birth to a physically or mentally disabled child, Fear of mood swings and Fear of changes in marital relations (p < 0.05) in comparison with control group. Conclusion. Holding pregnancy-training classes using group discussion method is a good strategy to reduce anxiety in pregnant women. Therefore, it is recommended that this educational strategy classes be used with mothers from the second trimester of pregnancy in urban family physician centers or those referred to a nearby clinic.